A compreensão da natureza da ciência a partir do estudo de radioatividade : contribuição de uma sequência de ensino-aprendizagem - Rocha, Jennyfer Alves (2018)
This research aimed to analyze the development of a Teaching-Learning Sequence (TLS) elaborated from the perspective of History and Philosophy of the Science, verifying how its contributions to the students' perception about the Nature of Science and conceptual elaboration around the theme radioactivity. The research was developed with 26 students from the 2o year of the High School of the College of Application, located in the municipality of São Cristovão, Sergipe. It presents a qualitative approach and It started from the hypothesis that a TLS constructed from a Contextual Approach can contribute to students' understanding of the Nature of Science. Data were collected through questionnaires and video recordings. The data from the video recordings were mapped originating episodes of the classroom, according to the methodology presented in Mortimer et al. (2007) and in Silva (2008) and together with the data obtained through the questionnaires were submitted to a Discursive Textual Analysis (MORAES; GALIAZZI, 2006). The discursive sequences that compound the episodes and the answers presented to the questionnaires were characterized considering emergent categories that reveal the students' understanding about aspects related to the Nature of Science and the concepts involved in the theme radioactivity. An analysis of the interactions developed throughout the TLS, as well as the data from the questionnaires, were fundamental to evidence the variety of meanings, for example, scientific methods. The teacher / researcher's investment in fostering classroom discussions, as well as the mediating tools used by her, favored the advancement of students' conceptions towards a rupture of stereotypes about the Nature of Science. Thus, it was observed that, in parallel to the conceptual advance regarding the subject of radioactivity, the TLS contributed positively to destabilize the empiric, linear, neutral and masculine conceptions of science, enabling the perception of this as a result of a community of historical practice and socially situated.